2022
DOI: 10.15585/mmwr.mm7126e1
|View full text |Cite
|
Sign up to set email alerts
|

Interim Analysis of Acute Hepatitis of Unknown Etiology in Children Aged <10 Years — United States, October 2021–June 2022

Abstract: asp § https://www.who.int/emergencies/disease-outbreak-news/item/2022-DON368 ¶ Adenovirus-positive results on respiratory, blood, or stool specimen types but excluded PUIs with pending or unknown test results (test results might not have been available at the time of data collection).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 8 publications
(8 reference statements)
0
32
0
3
Order By: Relevance
“…Initial epidemiological investigation and molecular testing have found adenovirus in 45-90% of severe acute hepatitis cases 6,[8][9][10][11] . In the UK, 116 of 179 (64.8%) reported cases as of May 2022 have tested positive for adenovirus 1 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Initial epidemiological investigation and molecular testing have found adenovirus in 45-90% of severe acute hepatitis cases 6,[8][9][10][11] . In the UK, 116 of 179 (64.8%) reported cases as of May 2022 have tested positive for adenovirus 1 .…”
Section: Discussionmentioning
confidence: 99%
“…Affected children were admitted to tertiary care hospitals in 6 states (Alabama, California, Florida, Illinois, North Carolina, and South Dakota) from October 1, 2021 to May 22, 2022 (Extended Data Table 1). Because many patients (12 of 16, 75%) were selected from those PUIs who tested positive for adenovirus and had samples submitted for adenovirus typing, PUIs with adenovirus infection may have been over-represented compared to the overall PUI population, of which adenovirus is detected in 45-90% 6,[8][9][10][11] . The median age of affected children was 3 years.…”
Section: Patient and Sample Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Before publishing this article, the most recent study stated that clinical data are required to determine the underlying causes of these patients’ illnesses and to evaluate any possible associations with adenovirus. It also highlighted the SARS-CoV-2 infection both before and after the patient’s illness began ( Cates et al, 2022 ). At present, anti-COVID-19 and symptom-relieving hepatitis medications are the most effective means to treat both prevention and symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…analysis showed that 26% of 123 children with unexplained hepatitis in the United States had tested positive for COVID-19 before their liver illness 2 . The CDC is now collecting the samples it needs to test for antibodies against SARS-CoV-2, to find out if other children with hepatitis had had infections that went undetected, says David Sugerman, a medical officer in the Division of Viral Diseases at the CDC's National Center for Immunization and Respiratory Diseases in Atlanta, Georgia.…”
mentioning
confidence: 99%